Overlapping vulnerabilities in workers of the electronics recycling industry formal sector: A commentary. Issue 11 (26th August 2020) - Ceballos, Diana M.; Côté, Daniel; Bakhiyi, Bouchra; Flynn, Michael A.; Zayed, Joseph; Gravel, Sabrina; Herrick, Robert F.; Labrèche, France
Abstract: Vulnerabilities in workers performing electronics recycling (e‐recycling) in the informal sector worldwide have been well documented. However, the growing e‐recycling industry in the formal sector still brings many challenges to protect the health of workers and their environment. This commentary aims to draw attention to the overlooked vulnerabilities faced by the workers of the e‐recycling industry formal sector in high‐income countries and discuss the potential impact on health inequalities experienced by these workers. Expanding the definition of vulnerability, not limited to the biological susceptibility to chemical and physical exposures, the demographic characteristics of workers in the e‐recycling formal sector often reveal social groups known to be disadvantaged regarding occupational exposures and health effects, including young workers, immigrant or ethnic minorities, and workers with mental or physical health issues or disabilities. Overlapping structural vulnerabilities of the e‐recycling industry stem from its newness, its working conditions, its conditions of employment, and the sociodemographic characteristics of its workforce. This phenomenon in high‐income countries is not restricted to the e‐recycling industry alone. It is rather a symptom of more generalized macro socioeconomical phenomena. The present challenges are in line with the new gig and green economies and changes in the global market, and their consequences on the solid waste sector. Continued efforts to strengthen the inclusion of social aspects of health into the complex interaction of the structural vulnerabilities met by e‐recycling workers will be essential to anticipate and prevent health issues in this essential but still emerging workforce.